Review—Modulation of Dielectric, Ferroelectric, and Piezoelectric Properties of Lead-Free BCZT Ceramics by Doping. (13th July 2021) - Verma, Ritesh; Chauhan, Ankush; Batoo, Khalid Mujasam; Jasrotia, Rohit; Sharma, Anand; Kumar, Rajesh; Hadi, Muhammad; Raslan, Emad H.; Labis, Joselito Puzon; Imran, Ahamad
Abstract : Barium calcium zirconate titanate (BCZT) is one of the most promising lead-free ceramic materials due to its superior electrical properties. BCZT exhibits the existence of morphotropic phase transition (MPB) and polymorphic phase transition (PPT) that are considered as the basis for superior piezoelectric and ferroelectric properties. It also exhibits a high piezoelectric constant (d33 ∼ 620pC/N) and a large remnant polarization (Pr ∼ 17. μ C cm −2 ). Due to the presence of a triple point, it also exhibits a high Curie temperature (TC ). These properties make BCZT a fascinating lead-free ceramic material for use in the electrical world. Here, we have studied the effect of doping on the modification of ferroelectric, dielectric, and piezoelectric properties. The modification of electrical properties caused by the change in phase transition temperature, and by structural modification and bulk formation are discussed.